Representation of Existential Crisis in the Song “33x” By Perunggu (Semiotic Analysis By Roland Barthes) - Febriana Dzulhijjah; Aghnia Dian Lestari (Salus Publica: Journal of Community Service, 2026)
In the context of modern society, developments in life marked by rapid information flows, social pressures, and demands for success often give rise to existential crises, especially among Gen Z. This generation often faces confusion in determining the direction of their lives, given the high social expectations placed upon them. Music serves as a medium capable of reflecting inner turmoil and existential experiences through song lyrics. This study aims to examine the representation of existential crises in the lyrics of the song “33x” by Perunggu using Roland Barthes' semiotic theory. The method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The analysis was carried out through the stages of denotation, connotation, and myth interpretation. The findings show that the song “33x” represents the existential crisis experienced by Gen Z, which is reflected through inner anxiety, loss of life orientation, and the process of searching for identity and meaning of existence. Supported by Jean-Paul Sartre's existentialism perspective, this song presents a picture of individual freedom as well as personal responsibility in determining the direction of life. In addition, there is a transcendental communication dimension that places the relationship between humans and God as a source of reflection, inner peace, and support in the journey of self discovery amid the pressures of modern life. Thus, the song “33x” does not merely serve as a means of entertainment, but also as a medium for self-reflection and inner communication for Gen Z in understanding and discovering their identity.